2022
DOI: 10.3389/fnins.2022.1007432
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mechanism of immediate analgesic effect of 1-time tuina intervention in minor chronic constriction injury rats using RNA-seq

Abstract: Previous studies have proved and investigated the mechanism of the analgesic effect of tuina treatment on neuropathic pain. The purpose of this study was to analyze changes in gene expression in the dorsal root ganglia (DRG) and spinal dorsal horn (SDH) after 1-time tuina intervention to investigate the immediate analgesic mechanism by tuina. An improvement in nociceptive behavior in minor chronic constriction injury (CCI) rats after 1-time tuina was observed. 1-time tuina was more effective in the amelioratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…In recent years, research on CAT for the treatment of NP has increased year by year, with a proliferation of systematic reviews, large-sample randomized controlled trials, and original studies. [31][32][33][34] However, bibliometric analyses of the disciplinary structure, status of study, and hotspots in the area are still vacant. Therefore, in this study, we summarized the general information of this research field by bibliometrics, and analyzed the contributions and collaborations of countries, institutions, and authors to the field.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, research on CAT for the treatment of NP has increased year by year, with a proliferation of systematic reviews, large-sample randomized controlled trials, and original studies. [31][32][33][34] However, bibliometric analyses of the disciplinary structure, status of study, and hotspots in the area are still vacant. Therefore, in this study, we summarized the general information of this research field by bibliometrics, and analyzed the contributions and collaborations of countries, institutions, and authors to the field.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the levels decreased after injection of TLR4 inhibitors in the model group and increased after administration of TLR4 activator in the tuina group. Wang et al (2022), using RNA-Seq, found that one-time tuina intervention could regulate TLR and NF-κB signaling pathways in minor chronic constriction injury (CCI) rats. It is suggested that tuina can reduce the expression of inflammatory factors by inhibiting the activation of TLR4/NF-κB signaling pathways, thereby achieving anti-inflammatory and analgesic effects.…”
Section: Tuina Exerts Analgesic Effects By Suppressing Peripheral Inf...mentioning
confidence: 99%
“…The method is simple, sensitive, accurate and can be used for the detection of amino acids and other neurotransmitters. 31 Previous studies of our research group Wang HR, etc., 32 the minor chronic constriction injury (minor CCI) rats were used as a model to simulate the clinical peripheral nerve injury research, found that the therapy of three manipulations and three acupoints instant can achieve the analgesic effect. To test the scientific hypothesis of how tuina achieves immediate pain relief, in this study, metabolomics was used to detect the changes of relevant neurotransmitters in the pain transmission pathway of minor CCI model rats, so as to explore the analgesic initiation mechanism of tuina treatment instant of peripheral nerve injury.…”
Section: Introductionmentioning
confidence: 99%